Emission and Heavy Metal Content Characteristic of Densified Refused Derived Fuels of Oil Sludge and Biomass Combination as an Alternative Fuel for Cement Plant - Rati Yuliar Ningsih; Fadjar Goembira; Puti Sri Komala; Nino Perdana Putra (Indonesian Journal of Environmental Management and Sustainability, 2019)
Hazardous Waste such Oil Sludge combined with biomass (coconut shell and rice husk) was utilized as an alternative fuel in cement plant in form of Densified-Refused Derived Fuel (D-RDF). D-RDF were Co-Processed with primary fuel into Rotary Kiln in order to reduce usage of fossil fuel and eliminate the hazardous waste by thermal treatment, meanwhile to recover the energy contained in the D-RDF, the utilization of these waste are expected without causing adverse effect into the environment. Co-Processing of D-RDF as alternative fuels into cement plant kiln must follow the regulation applied in Indonesian Environment and Forestry Minister regulation 19/2017 and European Union for Responsible Incineration and Treatment of Special Waste (EURITS). Based on previous research, D-RDF composition of oil sludge and biomass at 1:1 ratio with 5% starch addition was choose as they give best calorific value at 6000 kcal/kg. The objective of these research are to observe the emission caused by the utilization of these D-RDF and potential effect into cement or clinker product. The result show NOx and CO value are meet the standard requirement by government regulation meanwhile SO2 value which are 1251 mg/Nm3 and 1500 mg/Nm3, over the regulation standard which is 650 mg/Nm3. This issue could be overcome in the plant with pre treatment of D-RDF and utilization of Bag House Filter or Electostatic Precipitator before release the emission to the stack. Trace element analysis of D-RDF ashes (As, Cd, Co, Cr, Cu, Hg, Mn, Ni, Pb, Se, Sn dan Zn) show the result are meet the EURITS regulation, which mean utilization of D-RDF will not give quality deffect to cement or clinker product.